MODERNISASI PENGOLAHAN PAKAN BEBEK DENGAN MESIN PENGADUK DI PETERNAKAN TARET JAYA DESA AIR ANYIR KABUPATEN BANGKA - Saparin, Saparin; Wijianti, Eka Sari; Setiawan, Yudi; Suhdi, Suhdi; Rodiawan, Rodiawan; Ariksa, Jeri (Fakultas Teknik, Universitas Bangka Belitung, 2024)
Breeding ducks has several advantages, including: 1) the stages of raising ducks are easier; growth period; 2) duck growth is much faster, need 40 days to harvest; 3) marketing of meat and egg crops is easier; and 4) you can sell other parts to ducks, duck feathers for crafts and their droppings can be used as catfish feed. For laying ducks, their eggs can be harvested when they are 5 to 7 months old. Breeding ducks promises big enough profits that one of the livestock groups